Building Bodies, Constructing Selves - Sandra Louise Kaji-O'Grady; Sarah Manderson (Footprint)
Fitness gymnasiums shape subjects and establish communities. The extraordinary rise in the number of high-end, architect-designed fitness gymnasiums responds to, and accelerates market demand as individuals adapt to societal expectations. Yet going to the gym is not experienced as an external directive. It is felt as a desire to be one’s best, to live fully, to succeed. The central role played by design is to (re)produce the desire to voluntarily subject oneself to regimes of self-control and self-transformation. This article looks at how the diverse architecture and interior design of the fitness gymnasium creates this desire and constructs subject positions. Today’s gymnasiums reference elements of bathhouses, spas, surgical clinics, sanatoria, monasteries, discotheques and nightclubs, factories, homes, clubs, hotels, S&M dungeons, massage parlours, beauty salons, cafés, and, even, art galleries – albeit not all in one space. We analyse the richly diverse aesthetics of several commercial chains of gymnasiums and explore the affective experiences established through the manipulation of atmospheric qualities.